CHARACTERIZATION OF MACULAR NEOVASCULARIZATION IN BIETTI CRYSTALLINE DYSTROPHY USING MULTIMODAL IMAGING MODALITIES. Issue 4 (April 2023) - Li, Qian; Zhang, Shengjuan; Kang, Lihua; Wang, Donglin; Jiao, Xiaodong; Hejtmancik, J. Fielding; Wang, Lifei; Peng, Xiaoyan
Abstract : Supplemental Digital Content is Available in the Text. Complicated macular neovascularization (MNV) in Bietti crystalline dystrophy (BCD) was shown common with bilateral involvement on multimodal retinal imaging. The distribution and activities of the MNVs seemed to be associated with the primary chorioretinal compromise. Abstract : Purpose: To characterize the clinical features of macular neovascularization (MNV) secondary to Bietti crystalline dystrophy. Methods: The imaging data of 157 eyes in 79 patients with Bietti crystalline dystrophy were retrospectively reviewed. 12 individuals (19 eyes) were found to have MNVs. Multimodal retinal imaging was used to evaluate the features of MNVs and the primary chorioretinopathy. Results: The MNV lesions were shown as typical type 2 MNVs with subretinal hyperreflective material (SHRM), and usually detected along the borders of the retinal pigment epithelium/choriocapillaris dropout. The active MNVs were noted in earlier stages of Bietti crystalline dystrophy, while the activity was observed to be reduced in advanced cases. On spectral domain optical coherence tomography, the outer retinal structures were demonstrated to be partially preserved above the SHRMs compared with the extensive atrophy contiguously. Fibrotic scaring of the MNVs was commonly observed and arteriolarization was usually shown within the scars. Conclusion: MNV was demonstrated to be a common complication secondary to Bietti crystalline dystrophy. The lesions were typical type 2 MNV of varied activities possibly associated with the degrees of the primary degeneration. Choriocapillaris hypoperfusion may participate in MNV development.